Exploring communication skills training in undergraduate nurse education by means of a curriculum - Britt-Maj Wikström; Gunilla Svidén (MDPI AG, 2011)
This study is an attempt to investigate by means of a curriculum how nurses are trained theoretically and practically throughout their specialist education to communicate competently and professionally in interaction with colleagues and patients. Research today shows that there are many different approaches to develop professionally skilled communication in nurse-patient interaction. It indicates that this aspect of nurse education is regarded as an important feature by educators. It is therefore of interest to study, by means of analysing a curriculum, how nurses’ communicative competence is developed. To this purpose a curriculum was presented related to nursing communication skills training, selected from a University College of Health Care Sciences in Sweden. Both students and teachers need clearly defined curricula to structure their studies and to evaluate communication skills. The investigated curriculum could be further developed to direct students and teachers in effective communication skills. It is of importance to have a curriculum that could be interpreted in the same way by teachers and students.